1986
DOI: 10.1073/pnas.83.4.981
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of the 5'-leader sequence in coupling the stability of a human H3 histone mRNA with DNA replication.

Abstract: Two lines of evidence derived from fusion gene constructs indicate that sequences residing in the 5'-nontranslated region of a cell cycle-dependent human H3 histone mRNA are involved in the selective destabilization that occurs when DNA synthesis is terminated. The experimental approach was to construct chimeric genes in which fragments of the mRNA coding regions of the H3 histone gene were fused with fragments of genes not expressed in a cell cycle-dependent manner. After transfection in HeLa S3 cells with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
46
1

Year Published

1987
1987
1990
1990

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(48 citation statements)
references
References 43 publications
1
46
1
Order By: Relevance
“…This sequence is particularly noteworthy in light of the extremely high A+T content of noncoding regions in D. discoideum mRNAs (67). More definitive evidence for the importance of 5'-and 3'-UT regions has come from recent experiments in which these regions have been deleted, replaced, or transferred, resulting in substantial changes in the decay rates of individual mRNAs (22,42,53,64,74,76). The most well-characterized of the UT elements are the 3' AU-rich sequences associated with the GM-CSF mRNA (and other lymphokine and protooncogene mRNAs [12,50,74]) and the 3' stem-loop structure associated with the replication-dependent histone mRNAs (21,68 Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This sequence is particularly noteworthy in light of the extremely high A+T content of noncoding regions in D. discoideum mRNAs (67). More definitive evidence for the importance of 5'-and 3'-UT regions has come from recent experiments in which these regions have been deleted, replaced, or transferred, resulting in substantial changes in the decay rates of individual mRNAs (22,42,53,64,74,76). The most well-characterized of the UT elements are the 3' AU-rich sequences associated with the GM-CSF mRNA (and other lymphokine and protooncogene mRNAs [12,50,74]) and the 3' stem-loop structure associated with the replication-dependent histone mRNAs (21,68 Fig.…”
Section: Discussionmentioning
confidence: 99%
“…It is likely that these complex decay kinetics reflect the sum of the decay rates of individual mRNAs (e.g., in D. discoideum, the most stable mRNAs have half-lives of approximately 10 h and the least stable mRNAs have half-lives which are approximately 10-fold shorter). It has been suggested that such large differences in the stability of individual mRNAs could be accounted for by differences in their respective sizes (39,52,58,63,78,81), poly(A) tail lengths (8,28,56,91), ribosome loading (1,26,33,41,45), or 5'-and 3'-untranslated (UT) sequences (42,53,64,69,74,76,89). To test the validity of these hypotheses, we have identified cloned cDNAs which encode mRNAs that are representative of the stability extremes in D. discoideum and have initiated a characterization of the properties of the respective mRNAs.…”
mentioning
confidence: 99%
“…In human histone H3 mRNA, however, the 5' noncoding region is important in linking the stability of the histone mRNA to DNA synthesis (Morris et al, 1986).…”
Section: Mrna Turnovermentioning
confidence: 99%
“…Although we know that puromycin and cycloheximide have no effect on the acceleration of histone mRNA degradation induced by S130 and histone proteins (S.W.P., unpublished observations), we do not know how translation rates and polysome structure affect autoregulation. Since histone mRNA metabolism tends to be affected by most mutations that alter its 5' or 3' sequences or its intracellular location (4,7,13,26,39,43,59,60,66,75), we suggest that normal regulation of histone mRNA turnover is strictly dependent not only on the stem and loop but also on additional histone-specific sequences that specify how and where it is translated. The constraints placed on normal…”
mentioning
confidence: 99%